2021
DOI: 10.1101/2021.10.31.466575
|View full text |Cite
Preprint
|
Sign up to set email alerts
|

A feedback loop between heterochromatin and the nucleopore complex controls germ-cell to oocyte transition duringDrosophilaoogenesis

Abstract: SummaryGerm cells differentiate into oocytes that become totipotent upon fertilization. How the highly specialized oocyte acquires this distinct cell fate is poorly understood. During Drosophila oogenesis, H3K9me3 histone methyltransferase SETDB1 translocates from the cytoplasm to the nucleus of germ cells concurrent with oocyte specification. Here, we discovered that nuclear SETDB1 is required to silence a cohort of differentiation-promoting genes by mediating their heterochromatinization. Intriguingly, SETDB… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

4
20
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
3
2

Relationship

3
2

Authors

Journals

citations
Cited by 6 publications
(24 citation statements)
references
References 98 publications
4
20
0
Order By: Relevance
“…Our bulk RNA-seq data, as well as the available scRNA-seq data indicated that RpS19b was highly expressed in GSCs, decreased during differentiation in the cyst stages and was greatly decreased in expression in early egg chambers, consistent with previous reports ( Fig. 2 A,B) ( McCarthy et al, 2021 ; Sarkar et al, 2021 preprint). To further validate this expression pattern, we probed the expression of RpS19b in vivo using in situ hybridization as well as an RpS19b::GFP line that is under endogenous control elements ( McCarthy et al, 2021 ).…”
Section: Resultssupporting
confidence: 92%
See 1 more Smart Citation
“…Our bulk RNA-seq data, as well as the available scRNA-seq data indicated that RpS19b was highly expressed in GSCs, decreased during differentiation in the cyst stages and was greatly decreased in expression in early egg chambers, consistent with previous reports ( Fig. 2 A,B) ( McCarthy et al, 2021 ; Sarkar et al, 2021 preprint). To further validate this expression pattern, we probed the expression of RpS19b in vivo using in situ hybridization as well as an RpS19b::GFP line that is under endogenous control elements ( McCarthy et al, 2021 ).…”
Section: Resultssupporting
confidence: 92%
“…A modified in situ hybridization procedure for Drosophila ovaries was followed from Sarkar et al (2021) . Probes were designed and generated by LGC Biosearch Technologies using Stellaris ® RNA FISH Probe Designer, with specificity to target base pairs of target mRNAs.…”
Section: Methodsmentioning
confidence: 99%
“…To determine if the bulk RNA-seq data recapitulates genuine changes in gene expression, we compared the expression of ribosomal small subunit protein 19b ( RpS19b ) in bulk RNA-seq to scRNA-seq data. Our bulk RNA-seq data, as well as the available scRNA-seq data indicated that RpS19b was highly expressed in GSCs, decreased during differentiation in the cyst stages and was greatly decreased in expression in early egg chambers, consistent with previous reports ( Fig 2A-B ) (McCarthy et al, 2021; Sarkar et al, 2021). To further validate this expression pattern, we probed the expression of RpS19b in vivo using in situ hybridization as well as an RpS19b::GFP line that is under endogenous control elements (McCarthy et al, 2021).…”
Section: Resultssupporting
confidence: 92%
“…A modified in situ hybridization procedure for Drosophila ovaries was followed from Sarkar et al . (2021).…”
Section: Methodsmentioning
confidence: 99%
“…One type includes genes usually expressed in the testis [9]. A second class includes genes that are typically expressed in undifferentiated female germ cells but are silenced once the oocyte is specified, such as ribosomal protein S19b [70]. These few examples of context dependent H3K9me3 gene silencing suggest a finely tuned guidance mechanism in the female germline.…”
Section: Discussionmentioning
confidence: 99%